2005
DOI: 10.1038/sj.npp.1300864
|View full text |Cite
|
Sign up to set email alerts
|

Microinjection of Naltrexone into the Central, but not the Basolateral, Amygdala Blocks the Anxiolytic Effects of Diazepam in the Plus Maze

Abstract: The amygdala is involved in behavioral and physiological responses to fear, and the anxiolytic properties of several drugs are localized to this region. Activation of endogenous opioid systems is known to occur in response to stress and a growing body of literature suggests that opioid systems regulate the properties of anxiolytic drugs. These experiments sought to elucidate the role of opioid receptors in the central (CeA) and basolateral (BLA) nuclei of the amygdala in regulating the anxiolytic properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 74 publications
0
23
1
Order By: Relevance
“…The systemic administration of MOR and DOR receptor antagonists failed to modify the behavioral effects of DZ in this test. These results differ from previous findings demonstrating that the anxiolytic effects of DZ in the elevated plus maze test were attenuated by injections of the nonselective opioid receptor antagonist naltrexone into the central, but not the basolateral, amygdala (Kang et al 2000;Burghardt and Wilson 2006). These differences could be due to influences of systemically administered opioid receptor antagonists on DOR and MOR in several different brain areas that might be offsetting the amygdalar effects of these drugs, and/ or the use of receptor selective antagonists.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The systemic administration of MOR and DOR receptor antagonists failed to modify the behavioral effects of DZ in this test. These results differ from previous findings demonstrating that the anxiolytic effects of DZ in the elevated plus maze test were attenuated by injections of the nonselective opioid receptor antagonist naltrexone into the central, but not the basolateral, amygdala (Kang et al 2000;Burghardt and Wilson 2006). These differences could be due to influences of systemically administered opioid receptor antagonists on DOR and MOR in several different brain areas that might be offsetting the amygdalar effects of these drugs, and/ or the use of receptor selective antagonists.…”
Section: Discussioncontrasting
confidence: 57%
“…Non-selective antagonists (naloxone), however, can block the decreases in locomotor activity in mice after high but not low doses of chlordiazepoxide (Rodgers et al 1985). Further, we consistently observe that various treatments (benzodiazepine administration, opioid antagonists, chronic running) have distinct effects on the anxiety and activity measures in the elevated plus maze, suggesting that separate neural substrates underlie changes in these behavioral endpoints (Kang et al 2000;Burghardt et al 2004;Burghardt and Wilson 2006). The present data suggest that DOR is an integral component of the relationship between amygdalar ENK and diazepam on anxiety-related behaviors, but not activity-related behaviors.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The effects of enkephalin overexpression are reversed by systemic administration of the non-selective opioid receptor antagonist naloxone (Kang et al, 2000) and the DOR antagonist naltrindole (Primeaux et al, 2006). We have also shown that localized injections of the non-selective antagonist naltrexone in the CEA, but not the basolateral nucleus, attenuate the anxiolytic influences of diazepam in the elevated plus maze (Burghardt and Wilson, 2006).…”
Section: Introductionmentioning
confidence: 59%
“…The amygdala plays a key role in mood behaviors and emotional memory processes (Charney et al, 1998;Davis et al, 1994;Davis, 1992;Panksepp, 1990) in addition to being a key structure in mediating the anxiolytic effects of drugs such as benzodiazepines (BZs) Treit, 1995, 1994;Burghardt and Wilson, 2006;Petersen et al, 1985;Scheel-Kruger and Petersen, 1982;Senders and Shekhar, 1995;Menard and Treit, 1999;Kang et al, 2000). The endogenous opioid system also helps to mediate many responses associated with stress or anxiety (Panksepp, 1990;Drolet et al, 2001), and opioid processes in amygdala appear to play some role in the control of anxiety and the anxiolytic effects of BZs, although the opioid peptides and opioid receptor subtypes mediating such effects are unclear.…”
Section: Introductionmentioning
confidence: 99%